Enzymatic debridement: past, present, and future. Issue 4 (4th July 2022) - De Decker, Ignace; De Graeve, Liesl; Hoeksema, Henk; Monstrey, Stan; Verbelen, Jozef; De Coninck, Petra; Vanlerberghe, Els; Claes, Karel E. Y.
Abstract: Introduction: Early surgical debridement of the deep second and third-degree burns is still the standard of care (SOC) to prepare the wound bed for skin grafting. However, this technique has some drawbacks that explain the growing interest in enzymatic debridement as an alternative. In this article, we provide a historic overview as well as the current state-of-the-art and future prospective of this type of non-surgical debridement. Materials and methods: A narrative review of the available literature was conducted using a systematic search. Results: A total of 32 articles were included. The only enzyme mixture still used nowadays for burn eschar removal is bromelain-based. There is increasing evidence that this type of enzymatic debridement is a powerful tool to selectively remove the eschar in deep burns, thereby reducing the need for autologous skin grafting compared to surgical SOC. Moreover, off-label use of enzymatic debridement with NexoBrid ® (facial, pediatric, and >15%TBSA burns) has proven to be effective and safe. Conclusion: There is increasing evidence that bedside administered NexoBrid ®, preferably under regional anesthesia, is a powerful tool for selective burn eschar removal. However, the clinical wound bed evaluation post-NexoBrid ® procedure in relation to the optimal treatment decision—conservative treatment vs. surgery—is not yet completely elucidated. More high-quality prospective clinical trials are necessary to compare enzymatic debridement of objectively confirmed deep burns with the current standard treatment and assess the effectiveness of the eschar removal, the need for surgery, the healing time of such wounds, and the long-term scar quality.